Effect of Hyperbaric Oxygen Therapy Dose on Post-Replantation of the Distal Phalanx of Digiti II Manus Sinistra - Harnanik, Titut; Pradnyapramesti, Made Kanya Emeralda; Jayarta, Nyoman Sayang (Journal of Liaquat University of Medical & Health Sciences, 2025)
Finger replantation in adults requires a more extended healing period and is at risk of failure. Giving hyperbaric oxygen therapy (HBOT) at the correct dose can speed healing, reducing the risk of failure. A case involved a 32-year-old woman after replantation of the distal phalanx of digiti II manus sinistra of the patient who experienced cyanosis and necrosis. This report analyzes the relationship between HBOT dose and accelerated stimulation of growth factors that can improve the wound healing process. Replantation refers to the reconnection of an amputated body part to its anatomical structure to restore the function of the injured part. The outcome depends on the dose of HBOT, the patient's intrinsic factors, and the nature of the injury. Giving HBOT once a day, in this case, was not effective because the patient's fingertips became more cyanotic, and necrosis increased. Providing the correct dose of HBOT twice a day accelerates overcoming hypoxia. It helps successfully heal wounds through angiogenesis, collagen formation, and epithelialization, so new tissue growth is expected to accelerate.